1975
DOI: 10.1017/s0022172400046659
|View full text |Cite
|
Sign up to set email alerts
|

The production and preliminary investigation of Burulin, a new skin test reagent for Mycobacterium ulcerans infection

Abstract: SUMMARYThe preparation of a skin test antigen from Mycobacterium ulcerans by ultrasonic disintegration and filtration is described. The reagent, called Burulin, was tested in Africa in normal school children, and in patients with leprosy, tuberculosis or M. ulcerans disease. Those with tuberculosis or M. ulcerans disease were simultaneously tested with Tuberculin PPD. Burulin was found to be highly specific for patients in the reactive stage of M. ulcerans disease, and there was no cross-reaction in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 6 publications
(6 reference statements)
2
41
0
Order By: Relevance
“…On the other hand, in a more recent study, Phillips et al (27), using a higher number of patients, reported a strong expression of IFN-g in both nodular and ulcerative lesions. Also in line with our findings, supporting therefore the existence of protective cellular-mediated immune and delayed-type hypersensitivity responses, associated with IFN-g production in the context of Th1 responses, when BU disease progresses to healing, granuloma formation occurs (3,46,(53)(54)(55), and the positivity of the Burulin skin test increases (56)(57)(58). In addition, BCG vaccination was found to protect humans against BU osteomyelitis (59), and BCG or a DNA vaccine encoding Ag85A from BCG confer some degree of protection against M. ulcerans experimental infections (60,61).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, in a more recent study, Phillips et al (27), using a higher number of patients, reported a strong expression of IFN-g in both nodular and ulcerative lesions. Also in line with our findings, supporting therefore the existence of protective cellular-mediated immune and delayed-type hypersensitivity responses, associated with IFN-g production in the context of Th1 responses, when BU disease progresses to healing, granuloma formation occurs (3,46,(53)(54)(55), and the positivity of the Burulin skin test increases (56)(57)(58). In addition, BCG vaccination was found to protect humans against BU osteomyelitis (59), and BCG or a DNA vaccine encoding Ag85A from BCG confer some degree of protection against M. ulcerans experimental infections (60,61).…”
Section: Discussionsupporting
confidence: 91%
“…Because BUD is thought to mediate a selective suppression of human T-cell responses (21,23), which results in a reduced delayed-type hypersensitivity reaction to M. ulcerans proteins in patients until late in the course of disease (10,27), it has been thought that the detection of an immune response to infection and disease would not be diagnostic. Humoral im-munity, however, may be useful for the diagnosis of disease, since serum samples from infected individuals from several geographically distinct regions where BUD is endemic have shown high antibody titers to M. ulcerans antigens (10,12).…”
Section: Buruli Ulcer Disease (Bud) Is An Emerging Disease Caused By mentioning
confidence: 99%
“…The antigens were prepared by the method of Stanford et al (1975) using M. fortuitum, M. vaccae and two strains of M. avium originally isolated from tuberculous birds from Slimbridge. A secreted antigen of M. avium from culture nitrate, prepared by a method originally described for M. tuberculosis (Abou-Zeid et al, 1988), was also used.…”
Section: Elisamentioning
confidence: 99%